2004
DOI: 10.1007/s00421-004-1284-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance at altitude and angiotensin I-converting enzyme genotype

Abstract: The "insertion" (I) rather than "deletion" (D) variant of the human angiotensin-converting enzyme (ACE) gene is associated with both lower tissue ACE activity and elite performance at high altitude. We examined whether the onset of acute mountain sickness (AMS), and further performance on reaching the summit of Mt. Blanc are influenced by the ACE I/D polymorphism. Two hundred and eighty-four climbers (235 males, [37.0 (11.0 years], (86 DD, 142 ID, 56 II)) had assessment of their AMS status upon arrival to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…In contrast, two cohort studies of the ACE locus have suggested an I-allele performance benefit for mountaineers ascending to extreme altitude (Montgomery et al, 1998;Tsianos et al, 2005). The earlier study by Montgomery et al (1998) reported an overrepresentation of the I-allele in elite mountaineers who had ascended above 7000 m without the use of supplemental oxygen No climber in that study (out of 15) who managed to ascend beyond 8000 m without supplemental oxygen was of D/D genotype.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, two cohort studies of the ACE locus have suggested an I-allele performance benefit for mountaineers ascending to extreme altitude (Montgomery et al, 1998;Tsianos et al, 2005). The earlier study by Montgomery et al (1998) reported an overrepresentation of the I-allele in elite mountaineers who had ascended above 7000 m without the use of supplemental oxygen No climber in that study (out of 15) who managed to ascend beyond 8000 m without supplemental oxygen was of D/D genotype.…”
mentioning
confidence: 84%
“…The earlier study by Montgomery et al (1998) reported an overrepresentation of the I-allele in elite mountaineers who had ascended above 7000 m without the use of supplemental oxygen No climber in that study (out of 15) who managed to ascend beyond 8000 m without supplemental oxygen was of D/D genotype. In a follow-up prospective study with a much larger sample of recreational climbers (n ϭ 248) attempting to ascend Mont Blanc (4807 m), the I-allele again predicted success in reaching the summit (Tsianos et al, 2005). That is, the I-allele frequency was 0.47 in those who reached the summit versus 0.21 in those who failed to reach the summit (p ϭ 0.01).…”
mentioning
confidence: 97%
“…One of the most well studied gene polymorphisms in association with HAS is the angiotensin-converting enzyme (ACE) insertion/ deletion (rs4340) from the RAS system [48][49][50]. The ACE-I allele has been associated with superior performance benefit for mountaineers ascending to extreme altitude compared to the ACE-D allele [51,52], while the ACE -I/I genotype has been found to maintain higher arterial oxygen saturation at rest and during exercise at high altitude [53]. Perhaps the genetic reason for these findings is that the 288bp ACE-I allele generates at least 84 potential TFBS compared to the ACE-D allele which generates four TFBS (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…37 Özellikle elit uzun mesafe koşucular, kayakçı-lar ve dağcılarla yapılan birkaç çalışmada, ADE genindeki I alleli ile dayanıklılık performansının ilişkili olduğu saptanmıştır. 39,40,41,42 Fakat, karışık spor dalları ile yapılan çalışmalarda bu ilişki göste-rilememiştir. 7 Örneğin; Juffer ve ark.…”
Section: Anji̇yotensi̇n I-dönüştürücü Enzi̇m Geni̇unclassified